DAN INTERPERSONAL SKILL TERHADAP KINERJA MANAJER LINI - Merry Anggraeni (Jurnal Akuntansi Bisnis, 2012)
Manufacturing company is company that require high performance from everyone involved. One of which is the line managers responsible for work activities related to output or product, and oversees operational labors. Whether or not this performance is influenced by leadership style and interpersonal skill the leader of line managers. This study dicusses about different test of situasional Leadership Style on the performance of line managers with interpersonal skill as an interaction effect. The first hypothesis suggest that there is no performance difference between leadership style that fits and does not fit with condition of line managers. The result of the second hypothesis suggest that there is no performance difference between the categories of situational leadership style with the interpersonal skill as an interaction effect. Based on these results, it is expected that the company can improve the performance of line managers by not only applying situational leadership style that matches with the condition of line managers